Métaphore de l’Amour dans les Paroles de l’Album «D’eux» de Céline Dion (Universitas Negeri Semarang, 2021)
This research discusses the metaphorical elements contained in the song lyrics of Celine Dion's album D'Eux. From this study, it was found that there are 26 verses from 3 songs, titled